The Relationship Between Body Posture and Temporomandibular Disorder (TMD) in Online Game Players in Cimahi - Azkya Patria Nawawi; Mutiara Sukma Suntana; Baiq Febyana Hidayah Amanda (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Temporomandibular Disorder (TMD) is a musculoskeletal disorder that involves the temporomandibular joint (TMJ) and masticatory muscles, with symptoms such as pain, clicking sounds, and limited jaw movement. The etiology of TMD was multifactorial, one of which was Forward Head Posture (FHP), often triggered by poor body posture due to prolonged sitting, as in online gamers. This study aimed to determine the relationship between body posture (FHP) and Temporomandibular Disorder (TMD) in online gamers in Cimahi. Methods: A cross-sectional study was conducted on online gamers in the Cimahi area using consecutive sampling techniques, resulting in 35 online gamers who met the inclusion criteria. The Subjects were asked to complete the FAI questionnaire to assess TMD, and CVA measurements were taken to evaluate the FHP. Results and Discussions: A total of 51.4% of subjects were identified as experiencing mild TMD, and 54.3% had mild FHP. Spearman’s correlation test yielded p = 0.449 (p > 0.05), indicating no significant difference. Conclusions: Online gamers with a CVA ≤ 50, indicating mild FHP, were also identified as experiencing mild TMD.